Development of a water-injected twin-screw compressor for mechanical vapor compression desalination systems. (25th February 2016) - Shen, Jiubing; Xing, Ziwen; Zhang, Kai; He, Zhilong; Wang, Xiaolin
Highlights: A water-injected twin-screw compressor was developed for MVC systems. Performance of the water-injected twin-screw compressor was experimentally studied. Effect of key parameters on the compressor performance was investigated. Compressor speed and water injection flow rate had huge effects on the performance. The water-injected twin-screw compressor could operate reliably in the MVC system. Abstract: The water-injected twin-screw compressor is a key component in the mechanical vapor compression (MVC) desalination system, which is a promising technology for small and medium scale water production. This paper presents an experimental study on a water-injected twin-screw compressor. A prototype is developed and applied in a 50 m 3 /day double-effect MVC system. The effect of important parameters (including compressor rotation speed, water injection flow rate and compressor inlet temperature) on the compressor performance is experimentally investigated. It is found that the volumetric flow rate and power consumption of the compressor increases almost linearly with the rise in compressor rotation speed. Results also show that the compressor inlet temperature only affects the power consumption of the twin-screw compressor. It has minor effect on the volumetric flow rate, and volumetric and isentropic efficiencies of the compressor. Study further shows that water injection substantially reduces the compressor discharge temperature. As the water injection flow rate increases, the vapor compression process more closely approaches saturation vapor compression and hence the isentropic efficiency of the twin-screw compressor increases. The analyses demonstrate that the water-injected twin-screw compressor can be reliably operated in the MVC system with satisfactory system performance.